Effects of Sweet Flag Extracts (Acorus calamus L.) on Toxicity and the Levels of Esterase and Glutathione-S-transferase on the Brown Dog Tick (Rhipicephalus sanguineus (Latreille) - Leenuwongphun, Chanatda; Visetson, Suraphon; Milne, Manthana (วารสารวนศาสตร์ไทย, 2022)
The tendency of herbal extracts as insecticide alternative is gaining high acceptability to Thai people. Some synthetic pesticides namely pyrethroids and organophosphate have been causing detrimental effects to home pet such as dogs. This research was done to evaluate the efficiency of sweet flag (Acorus calamus L.) rhizomes that have been proved to repel and give mortality to some insects. Sweet flag rhizomes was extracted by soaking method at room temperature using 95% ethanol was trialed. The dipping method of herbal extracts was used against brown dog tick (Rhipicephalus sanguineus). The completely randomized designs (CRD) with 4 replicates were to analyse their LC50. The toxicity of sweet flag extracts showed Y = 7.28 + 28.65X; LC50 ca. 1.49% w/v. after exposure at 24 hours and after exposure for 36 hours was Y = 10.91 + 34.50X; LC50 ca. 1.13% w/v. on nymph brown dog tick and Y = 18.36 + 29.48X; LC50 ca. 1.07% w/v. after exposure at 24 hours and after exposure for 36 hours was Y =21.28 + 33.34X; LC50 ca. 0.86% w/v. on adult brown dog tick. The detoxification enzyme activities of esterase and glutathione-S-transferase from brown dog tick after 24 hours exposure were also observed. esterase showed stronger activity than other enzymes. The enzyme activities of esterase and glutathione-S-transferase from brown dog tick after 24 hours were induced follow levels of sweet flag extract was increased. Keywords: Efficiency, Sweet flag extracts, Brown dog tick, Esterase, Glutathione-S-transferase